2005
DOI: 10.1128/aem.71.12.8966-8969.2005
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Induced Sequence Artifacts and Bias: Insights from Comparison of Two 16S rRNA Clone Libraries Constructed from the Same Sample

Abstract: The contribution of PCR artifacts to 16S rRNA gene sequence diversity from a complex bacterioplankton sample was estimated. Taq DNA polymerase errors were found to be the dominant sequence artifact but could be constrained by clustering the sequences into 99% sequence similarity groups. Other artifacts (chimeras and heteroduplex molecules) were significantly reduced by employing modified amplification protocols. Surprisingly, no skew in sequence types was detected in the two libraries constructed from PCR prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
451
4
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(483 citation statements)
references
References 39 publications
12
451
4
5
Order By: Relevance
“…The clone library was not used in this work for covariation analysis because of its qualitative nature and the uncertainty of its reproducibility (25)(26)(27). However, with the rapid development of high-throughput sequencing techniques (12,28), sequencing-based analysis will eventually become quantitative and cost-effective enough for this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The clone library was not used in this work for covariation analysis because of its qualitative nature and the uncertainty of its reproducibility (25)(26)(27). However, with the rapid development of high-throughput sequencing techniques (12,28), sequencing-based analysis will eventually become quantitative and cost-effective enough for this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of this is certainly owing to PCR-induced sequencing artefacts. For example, we have shown that the fraction of unique sequences was reduced from 76 to 48% when sequence artefacts were constrained in a large 16S rRNA library (Acinas et al 2004(Acinas et al , 2005. However, this is still a high fraction of unique sequences considering that the 16S rRNAs are evolutionarily highly conserved.…”
Section: Patterns Of Microbial Diversitymentioning
confidence: 99%
“…If these repetitive procedures confirmed the double signals in the reads, PCR products were cloned following the same protocol a s u s e d f o r t h e s e p a r a t i o n o f t h e n a t i v e a n d contaminating DNA fragments. The resulting clones were checked for errors, e.g., as those reported by Speksnijder et al (2001) and Acinas et al (2005), against the alignment of the approved direct sequences. Clones with unique nucleotides or gaps in the conservative sites were disregarded.…”
Section: Taxonomic Scopementioning
confidence: 99%